2023
DOI: 10.21203/rs.3.rs-2388979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA UCA1 promotes keratinocyte inflammation via suppressing METTL14 and activating the HIF-1α/NF-κB axis in psoriasis

Abstract: Psoriatic inflammation can be regulated by epigenetic factors, but little is known about their role. This work aims to reveal the effects of lncRNA UCA1 in keratinocyte inflammation. UCA1 was a psoriasis-related lncRNA in eight GEO transcriptome datasets and psoriatic skin. When we over-expressed or knocked down UCA1 in the keratinocyte cell line (HaCaT), the transcriptome and proteomic data showed that UCA1 could positively regulate inflammatory functions, such as response to cytokine. Experimental findings c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…also showed that the inhibition of PVT1 exon 2 could induce the growth suppression of cutaneous squamous cell carcinoma, which was caused by cellular senescence, increased p21/CDKN1A expression and cell cycle arrest 36 . However, besides skin tumors, lncRNAs also influence the pathogenesis of many skin inflammatory diseases, 33 such as psoriasis, 38–41 hidradenitis suppurativa, 42,43 atopic dermatitis 44–46 . Among these skin diseases, the psoriasis was the most studied one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also showed that the inhibition of PVT1 exon 2 could induce the growth suppression of cutaneous squamous cell carcinoma, which was caused by cellular senescence, increased p21/CDKN1A expression and cell cycle arrest 36 . However, besides skin tumors, lncRNAs also influence the pathogenesis of many skin inflammatory diseases, 33 such as psoriasis, 38–41 hidradenitis suppurativa, 42,43 atopic dermatitis 44–46 . Among these skin diseases, the psoriasis was the most studied one.…”
Section: Discussionmentioning
confidence: 99%
“…Among these skin diseases, the psoriasis was the most studied one. LncRNAs including lncRNA UCA1, 38 lncRNA BLACAT1 39 and LINC00958 41 could affect the destination of keratinocytes and then determine the process of psoriasis. Therefore, lncRNAs not only play a role in cutaneous carcinogenesis but influence the pathogenesis of non‐tumorous skin diseases.…”
Section: Discussionmentioning
confidence: 99%